Ultrasound-Assisted Extraction of Isoquercetin from Ephedra alata (Decne): Optimization Using Response Surface Methodology and In Vitro Bioactivities - Ezzouhra El Maaiden; Nagib Qarah; Amine Ezzariai; Adil Mazar; Boubker Nasser; Khadija Moustaid; Hassan Boukcim; Abdelaziz Hirich; Lamfeddal Kouisni; Youssef El Kharrassi (MDPI AG, 2023)
Isoquercetin (ISQ) is reported to be a powerful antioxidant with extremely high bioavailability and structural stability compared to aglycone quercetin. Despite this, it is not well studied due to the limited methods for its extraction. With the growing interest in the research and analysis of ISQ-rich herbs, there is a need to optimize an efficient and rapid method for their extraction. In the present study, the ultrasound-assisted extraction of ISQ from Ephedra alata Decne was optimized by a response surface methodology (RSM) using high-performance liquid chromatography as a separation method. The best possible ranges for extraction time (10-30 min), temperature (50-70 °C), ultrasonic power (60-90 W), solvent-to-solid ratio (50-70 mL/g), and ethanol concentration (50-70%) were determined using a single factor analysis. Subsequently, an optimization of the extraction conditions was performed with RSM using the Box-Behnken design. An ultrasonication time of 10 min, a temperature of 60 °C, a power of 75 W, a solvent-to-solid ratio of 60 mL/g, and an ethanol concentration of 70% were determined to be the optimal conditions for the highest recovery of isoquercetin (1033.96 ± 3.28 µg/g). Furthermore, E. alata powder morphology (using a scanning electron microscope), antioxidant activities, and the inhibition potential of key enzymes involved in skin aging (elastase and collagenase), hyperpigmentation (tyrosinase), diabetes (α-amylase), inflammation (hyaluronidase), and neurodegenerative disorders (cholinesterase) were determined and compared with those using the Soxhlet method. This study established a highly efficient method for ISQ extraction and suggested several potential applications of ISQ in the pharmaceutical and cosmetics industries.